2016
DOI: 10.1186/s13044-016-0030-1
|View full text |Cite
|
Sign up to set email alerts
|

Pendulum swings from hypo- to hyperthyroidism: thyrotoxicosis after severe hypothyroidism following neck irradiation in a patient with a history of Hodgkin’s lymphoma

Abstract: BackgroundA change in a thyrometabolic state from severe hypothyroidism to thyrotoxicosis is very uncommon, but possible in some circumstances.Case presentationA 27-year old female presented with clinical and biochemical thyrotoxicosis with a previous history chemo- and radiotherapy (including the neck region) for a Hodgkin’s lymphoma (at the age of 18). At the age of 20 this was followed by severe hypothyrodism [TSH > 100 μIU/mL (reference range: 0.27–4.2)]. She was stated on L-thyroxine, but the dose was lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Khatiwada et al observed significantly lower iron levels in hypothyroid Nepalese children and a strong correlation between iron deficiency and anemia with hypothyroidism. Anemic children tended to have higher TSH and iron deficient children had significantly lower fT3 levels than iron sufficient children [ 82 ].…”
Section: Intestinal Influences On the Thyroidmentioning
confidence: 99%
“…Khatiwada et al observed significantly lower iron levels in hypothyroid Nepalese children and a strong correlation between iron deficiency and anemia with hypothyroidism. Anemic children tended to have higher TSH and iron deficient children had significantly lower fT3 levels than iron sufficient children [ 82 ].…”
Section: Intestinal Influences On the Thyroidmentioning
confidence: 99%
“…There are reports, that after neck irradiation, Graves' disease (GD), an autoimmune disease may develop in patients previously being treated for hypothyroidism and interestingly one third of patients with Graves' hyperthyroidism had received thyroxine treatment before its onset [2]. Therefore thyroid hormone-replacement therapy in patients with hypothyroidism after irradiation of the neck does not always eliminate the risk of other thyroid abnormalities, including GD at a later date [4]. It is postulated that thyroiditis observed in Hodgkin's disease may be the result of immune regulation dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that genetically susceptible individuals may require an external trigger to switch from autoimmune hypothyroidism to Graves’ disease, such as an infection or neck irradiation ( 10 ), which would cause the balance to shift from TSH receptor-blocking antibodies to TSH receptor-stimulating antibodies. This phenomenon may not be as rare as previously thought and the physicians should be aware of this possibility if someone with a previously well-established hypothyroidism is now requiring less or no thyroid hormone replacement, and the TFTs keep demonstrating an overactive picture with no obvious reason, even many years after the diagnosis of hypothyroidism as in this case.…”
Section: Discussionmentioning
confidence: 99%